2014
DOI: 10.1111/nep.12255
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent glomerular disease after kidney transplantation: An update of selected areas and the impact of protocol biopsy

Abstract: ABSTRACT:Recurrence of native kidney disease following kidney transplantation affects between 10% and 20% of patients, and accounts for up to 8% of graft failures. In a considerable number of recipients with transplant glomerulopathy, it is impossible to distinguish between recurrent and de novo types. An accurate estimate of the incidence of recurrence is difficult due to limitations in the diagnosis of recurrent glomerulonephritis. De novo glomerular lesions may be misclassified if histological confirmation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 32 publications
1
25
1
4
Order By: Relevance
“…Such a finding is consistent with those published by Morozumi and associates and Moroni and associates, who found that recurrence of native kidney disease after kidney transplant affects between 10% and 20% of patients and accounts for up to 8% of graft failures. 25,26 Regarding the frequency of recurrent glomerular disease in kidney allograft, we found that focal segmental glomerulosclerosis and membranoproliferative glomerulonephritis are the most common recurrent diseases in the renal allograft with frequency of 10.5%. For focal segmental glomerulosclerosis, this rate is considered lower than recurrence rates reported by other studies, including Shimizu and associates 27 who reported recurrent focal segmental glomerulosclerosis in about 30% of studied recipients.…”
Section: Discussionmentioning
confidence: 97%
“…Such a finding is consistent with those published by Morozumi and associates and Moroni and associates, who found that recurrence of native kidney disease after kidney transplant affects between 10% and 20% of patients and accounts for up to 8% of graft failures. 25,26 Regarding the frequency of recurrent glomerular disease in kidney allograft, we found that focal segmental glomerulosclerosis and membranoproliferative glomerulonephritis are the most common recurrent diseases in the renal allograft with frequency of 10.5%. For focal segmental glomerulosclerosis, this rate is considered lower than recurrence rates reported by other studies, including Shimizu and associates 27 who reported recurrent focal segmental glomerulosclerosis in about 30% of studied recipients.…”
Section: Discussionmentioning
confidence: 97%
“…Studies on recurrent disease are difficult because not all patients had native kidney biopsies for ESRD diagnosis and most centers perform graft biopsies only when there are abnormal clinical or laboratory features. Hence, reported incidences of recurrent disease are influenced by clinical practices and could over‐ or underestimate its true occurrence . In this regard, it may be impossible to differentiate between de novo and recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, reported incidences of recurrent disease are influenced by clinical practices and could over-or underestimate its true occurrence. 6,7 In this regard, it may be impossible to differentiate between de novo and recurrent disease. Delaying txp until disease is inactive in cases of SLE or ANCA-mediated GN has been suggested and at our center we follow that practice with very low rates of recurrence of those diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Protocol biopsy facilitates early diagnosis of de novo and recurrent kidney disease (Morozumi et al, 2014) and therefore one or sometimes multiple protocol biopsies several months to a year after kidney transplantation are performed in several programs. Specific indications for protocol biopsies have been proposed (Racusen, 2006).…”
Section: Introductionmentioning
confidence: 99%